Teologi Agama-Agama Menurut Pemikiran Lesslie Newbigin Dan Johan Herman Bavinck - Doni Herwanto Harianja (STTRII, 2021)
This article is a comparative overview of the theology of religions according to the views of Lesslie Newbigin and Johan Herman Bavinck. Although these two missionaries are rooted in the tradition of Reformed theology, they both have different views in examining the theology of religions. Newbigin in analyzing religions tends to be negative so that Newbigin expresses an urgent urge to proclaim the gospel. Meanwhile, Bavinck tends to be positive in examining religions and does not provide an urgent encouragement in proclaiming the Gospel. At the end of this article, the author concludes that the views of each missionary figure should be embraced to obtain a more comprehensive and whole understanding in analyzing the theology of religions.